Disentangling the Leiothrix angustifolia species complex (Eriocaulaceae), with the description of three new endemic species from the Chapada Diamantina (Bahia, Brazil): L. chapadensis, L. montana and L. sincorensis - Giulietti, Ana Maria; Watanabe, Mauricio Takashi C.; Guerra, Gabriel Costa; Marinho, Lucas; Harley, Raymond M.; Zappi, Daniela Cristina (Phytotaxa, 2026)
Paepalanthus angustifolius with flat leaves and P. schlechtendalii with conduplicate leaves were described by Friedrich Körnicke more than 150 years ago, from collections by Blanchet from the Chapada Diamantina, Bahia, Brazil. Afterwards, those species were transferred to the genus Leiothrix. Based on the type-specimen analyses and new collections from the Chapada Diamantina, including a closely related L. rufula, we propose the epitypification of L. angustifolia, together with a more narrow circumscription of this species, and recognize three new species: L. chapadensis, L. montana and L. sincorensis, endemic to the same region. We present an identification key to the species, full descriptions, illustrations, and preliminary conservation status assessments. Comments on the Blanchet collection in the Chapada Diamantina region are also provided.